Exploration of Learning Style Preferences Among High School Students in the Context of Physics Education: An Empirical Analysis Using Kolb's Learning Style Inventory (KLSI) - Zaky, Muhammad; Untara, Ketut Alit Adi; Tang, Indo; Alfito, Alfito; Waenggo, Olivia (Universitas Lambung Mangkurat, 2024)
This study aimed to analyze the distribution of students' styles in learning Physics using the Kolb Learning Style Inventory (KLSI) in two different classes, namely XD and XG. The analysis results reveal that the Converger learning style is the most dominant, with 55.17% of students in XD and 73.53% in XG. The Converger learning style, characterized by a tendency for logical thinking and the ability to apply theory in practical contexts, is highly relevant in Physics education, which requires strong conceptual understanding and problem-solving applications. In addition, Converger, Accommodator, Diverger, and Assimilator learning styles were also identified, albeit in smaller numbers, with varying percentages across the XD and XG classes. This study reveals that the dominance of the Converger learning style in both classes suggests a strong alignment between current Physics teaching methods and the learning preferences of the majority of students. However, the presence of other learning styles underscores the importance of adopting diverse teaching strategies to ensure that all students, regardless of their learning style, are engaged and achieve optimal learning outcomes. This study also supports previous findings which proved that the Converger learning style is particularly effective in subjects that require analytical thinking and practical application, such as Physics. The implications of these findings advocate for developing more inclusive and adaptive teaching methods, integrating approaches that cater to all learning styles in the classroom.